Onset of room temperature ferromagnetism by plastic deformation in three paramagnetic pure metals. (June 2016) - Cepeda-Jiménez, C.M.; Hernando, A.; Barandiarán, J.M.; Pérez-Prado, M.T.
Abstract: This work shows that plastic deformation may trigger a spontaneous magnetization at ambient temperature in pure paramagnetic metals such as zirconium, titanium and magnesium. Subsequent strain relaxation by annealing leads to a decrease of the permanent magnetization. We propose that the lattice distortions associated with dislocations promote the emergence of ferromagnetism at the nanometric scale. Evidence for this explanation is the simultaneous observation, in pure Zr, which in the undeformed state exhibits Pauli paramagnetism, of a decrease in the susceptibility and of the absolute value of the magnetization at high fields with increasing deformation. Graphical abstract: Comparison of the room temperature magnetic behavior of pure Zr in the as-received condition (rolled and annealed) and after severe plastic deformation (ε ~ 6).